1999
DOI: 10.1002/(sici)1521-4141(199905)29:05<1435::aid-immu1435>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-C inhibits β1 integrin-dependent T lymphocyte adhesion to fibronectin through the binding of its fnIII 1 – 5 repeats to fibronectin

Abstract: The extracellular matrix consists of different proteins interacting to form a meshwork-like structure. T lymphocyte adhesion to individual matrix proteins is mainly regulated at the adhesion receptor level, but it is conceivable that the composition of the matrix itself may affect T lymphocyte adhesion to individual proteins. We have addressed the latter point by studying the effect of the matrix protein tenascin-C (TN-C) on T lymphocyte adhesion to fibronectin. Here we report that TN-C inhibits adhesion of T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 40 publications
(30 reference statements)
0
39
0
Order By: Relevance
“…This has also been reported in tumors. 31 Two mutually enhancing factors may play a role: TN-C can suppress CD3-mediated T-cell activation, [22][23][24]34,41 while activated CD3+ T-lymphocytes induce plasminogen-dependent proteolysis of TN-C by secreting u-PA. 20 Both may have a negative impact on the progression of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…This has also been reported in tumors. 31 Two mutually enhancing factors may play a role: TN-C can suppress CD3-mediated T-cell activation, [22][23][24]34,41 while activated CD3+ T-lymphocytes induce plasminogen-dependent proteolysis of TN-C by secreting u-PA. 20 Both may have a negative impact on the progression of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, tenascin-C interferes with cell adhesion on fibronectin (Chiquet-Ehrismann et al, 1988;Hauzenberger et al, 1999;Huang et al, 2001). To test whether tenascin-C modulates cell adhesion and proliferation of normal fibroblasts in a fibronectin context, we plated cells on a mixed substratum of fibronectin and tenascin-C. Phalloidin staining revealed that cell spreading was markedly disturbed in REF52 cells 1 h after plating on the mixed substratum ( Figure Figure 2b).…”
Section: Tenascin-c Is Antiadhesive For Anchorage-dependent Fibroblasmentioning
confidence: 93%
“…Recently, tenascin-C was identified as a prognostic marker for tumor recurrence and shown to play a role in glioblastoma growth and invasion (29). Tenascin-C inhibits b1-integrin-dependent T lymphocyte adhesion to fibronectin (34) and thus potentially inhibits the transmigration processes of Jurkat cells across glioblastoma cells. This speculation is supported by the finding that suppression of tenascin-C in glioma cells using the shRNA technique enhanced the transmigration rate of Jurkat cells and CD3/CD28-activated T cells in our transwell assay.…”
Section: Discussionmentioning
confidence: 99%